Regional Modelling for Optimal Allocation of Agricultural Crops Considering Environmental Impacts, Housing Value and Leisure Preferences. - Nava Haruvy; Sarit Shalhevet (European Regional Science Association (ERSA), 2006)
Regional planning should consider the impact of agricultural crops on housing value and leisure, as well as on the local environment. We designed an optimization model for allocating agricultural crops based on farmers profits as well as the impact on these three factors. Each crop creates a different landscape, as well as a different effect on shading and noise reduction. These in turn influence the value of nearby housing and the regional leisure opportunities. Each crop also has a positive and negative environmental impact, including potential use of treated wastewater as well as the effects of pesticides and fertilizers. All these factors were combined with economic considerations to suggest the optimal regional allocation of agricultural crops.
Keywords: 330